Adaptive or Transactional Leadership in Current Higher Education: A Brief Comparison - Khan, Natalie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
Higher education institutions operate in a complex environment that includes influence from external factors, new technologies for teaching and learning, globalization, and changing student demographics to name a few. Maneuvering such complexity and change requires a leadership strategy that is flexible and supportive. This paper reviews two leadership theories in reference to this need: adaptive leadership theory and transactional leadership theory. Three conceptual categories of environmental readiness, leadership complexity, and followers’ motivation are used as points of comparison for each theory. A recommendation is made for leadership strategy in higher education institutions based on this comparison.